2021
DOI: 10.3390/vetsci8030040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Novice and Experienced Surgeons Performing Corrective Osteotomy with Patient-Specific Guides in Dogs Based on Resulting Position Accuracy

Abstract: Corrective osteotomy has been applied to realign and stabilize the bones of dogs with lameness. However, corrective osteotomy for angular deformities requires substantial surgical experience for planning and performing accurate osteotomy. Three-dimensional printed patient-specific guides (3D-PSGs) were developed to overcome perioperative difficulties. In addition, novices can easily use these guides for performing accurate corrective osteotomy. We compared the postoperative results of corrective osteotomy accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… Year Authors Journal Case number Research type Type of surgery Results 2021 Rho YH et al. [ 127 ] Vet Sci 8 dog A cutting guide and reduction guide for corrective osteotomy It is useful for novice surgeons to accurately perform corrective osteotomy in dogs without complications. 2021 Caiti G et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
See 1 more Smart Citation
“… Year Authors Journal Case number Research type Type of surgery Results 2021 Rho YH et al. [ 127 ] Vet Sci 8 dog A cutting guide and reduction guide for corrective osteotomy It is useful for novice surgeons to accurately perform corrective osteotomy in dogs without complications. 2021 Caiti G et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…The template-guided MIPPO group was found to have greater surgical accuracy, with less variation in femoral length, anatomical lateral distal femoral angle (aLDFA), anatomical posterior distal femoral angle (aPDFA), and anteversion angle, with neater alignment and more significant advantages. In addition, the assistance of the guide can reduce the gap between novice and experienced surgeons [ 127 ].…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…As in our study, results of these studies showed that there was no significant difference between the novice and expert surgeon. 20,21 It is interesting to note that besides our study, only one study has compared lumbosacral pedicle screw placement with use of the 3D-PSG and the freehand technique. 10 This study found no difference between rates of medial pedicle wall perforation and based on their results, the study group was unable to recommend the use of 3D-PSG to help increase accuracy.…”
Section: Discussionmentioning
confidence: 94%
“…It is unlikely that the tumor grew aggressively, or that an error in the process of producing guides and prostheses occurred, because there was no problem in the contact of the resection guide and endoprosthesis. It is possible that errors occurred in the process of identifying tumor invasion into the bone, including the transformation of the DICOM files and the identification of the tumor in the 3D program [ 25 ]. Moreover, CT should be acquired with a slice thickness of 0.5 mm or less to accurately specify the location and size of tumors.…”
Section: Discussionmentioning
confidence: 99%